Investigation of TanDEM-X penetration depth over the Greenland ice - Abdullahi, Sahra; Wessel, Birgit; Leichtle, Tobias; Huber, Martin; Wohlfart, Christian; Roth, Achim (2018)
Ongoing global warming causes dramatic changes globally, especially with respect to Polar Regions. In this context, digital elevation data is of high importance for most glaciological applications. In this paper, we investigate TanDEM-X Penetration depth over snow and ice on the Greenland ice sheet. In particular, the relation of backscatter intensity and interferometric coherence to penetration depth of the X-band InSAR signal is explored in order to improve the reliability of TanDEM-X elevation data. The analyses showed a distinct relationship of backscatter intensity, coherence and penetration depth. In addition, the influence of the height of ambiguity of the interferometric TanDEM-X data is presented. On an experimental test site in Northern Greenland, we demonstrated the estimation of TanDEM-X penetration depth based on backscatter intensity and interferometric coherence utilizing a linear regression model.